P607 The Faroese IBD Study: Update on incidence from 2015–2020 and prevalence from 1960–2020. (27th May 2021) - Nielsen, K R; Midjord, J; Hammer, T; Lophaven, S; Burisch, J
Abstract: Background: Previous reports have found that the Faroe Islands has the highest reported incidence of inflammatory bowel disease (IBD) in the world. 1, 2 The purpose of this study was to update our previous work on the IBD incidence from 1960–2014 2 with data up until 2020 and to describe the prevalence of IBD over 60 years. Methods: All cases of Crohn's disease (CD), ulcerative colitis (UC) and IBD unclassified (IBDU) diagnosed between 1960 to 2020, including all age groups and year of death, were retrieved from the Medical Centre at the National Hospital of the Faroe Islands. Diagnoses were ascertained according to the Copenhagen Diagnostic Criteria. Population data from 1960–2020 were retrieved from Statistics Denmark and Statistics Faroe Islands. Point prevalence rates (per 100, 000) were estimated as all IBD patients alive and living in the Faroe Islands by the end of 1960, 1970, 1980, 1990, 2000, 2010 and 2020, divided by the Faroese population (end of year). Results: 232 individuals have been diagnosed with IBD during the past 6 years in the Faroe Islands: 29 (12%) with CD, 111 (48%) with UC and 92 (40%) with IBDU, resulting in an increased age-standardised IBD incidence rate (European Standard Population, ESP) from 74 per 100, 000 person-years (py) in 2010–14 to 80 in 2015–20. Figure 1 illustrates the updated IBD incidence rate integrated with results from our previous study. 2 The point prevalence rate of IBD was 5, 8 cases per 100, 000 persons in 1960; 46, 6 in 1970; 133, 9 in 1980; 325, 4 in 1990; 610, 7 in 2000; 925, 1 in 2010 and 1407, 9 cases per 100, 000 in 2020, corresponding to 1, 4% of the Faroese population living with IBD in 2020 compared to 0, 6% in 2000. Conclusion: The increasing incidence of IBD from 2015–2020 is mainly driven by IBDU, accounting for 40% of all cases and has increased from 21 per 100, 000 (ESP) in 2010–14 to 32 in 2015–2020. The age-standardised incidence rate of CD remains unchanged compared to our previous study, at 10 per 100, 000 (ESP), while the incidence of UC has decreased from 44 to 39 per 100, 000 (ESP). The prevalence of IBD has increased radically in accordance with the increasing incidence. Further investigations into the high proportion of IBDU and causes of the observed IBD pattern is currently ongoing. 1. Ng SC, Shi HY, Hamidi N, et al. Worldwide incidence and prevalence of inflammatory bowel disease in the 21st century: a systematic review of population-based studies. Lancet 2018;390:2769–78.et al. 2. The Faroese IBD Study: Incidence of Inflammatory Bowel Diseases Across 54 Years of Population-based Data. J Crohns Colitis 2016;10:934–42.